Early Economic Recovery: A Methodological Approach for Reconstruction and Development in Syria (Damascus University Journal for the economic and Political sciences, 2021)
This research reviews the various opinions that addressed the early economic recovery and discusses the terminological & processing overlap with other concepts such as reconstruction and state building. It then proceeds to study the post-conflict economic recovery approaches, that remained controversial given the relative newness of the concept and the lack of consensus regarding the use of those approaches, which are developed jointly between local and international stakeholders to ensure consistency with the country situation.Moreover, the research discusses the different views about sequencing and prioritization, which is considered the most problematic issue when designing a reconstruction strategy, according to the congestion of simultaneous needs in light of limited funding, capacity and time. The research also indicates that there is no agreement between the competing approaches on what the priorities and sequencing, but there is consensus that obtaining the correct sequence is central to the success of economic recovery and peace sustainability. While achieving this remains subject to the interactions and interventions of external stakeholders.Finally, the research presents a set of recommendations summarized by a proposed methodological approach to managing the early economic recovery and reconstruction in Syria, accompanied by strategic, institutional and financial frameworks to control the phase and to ensure efficiency, effectiveness and transparency. With reference to the most prominent challenges represented by the insufficient financial resources and achieve a narrow economic recovery, in which elites and warlords enhance their wealth without regard for the broad segment of poor.
Keywords: Economic Recovery; Early Recovery; Reconstruction; Economic Policy; Economic & Institution Reform; Political Economy; Strategic Planning